LC-MS/MS Method Applied to the Detection and Quantification of Ursodeoxycholic Acid Related Substances in Raw Material and Pharmaceutical Formulation - Boscolo, Oriana (2018)
Abstract: Objective: To develop a highly sensitive LC-MS/MS (liquid chromatography-mass spectrometry/mass spectrometry)method applied to the detection and quantitation of UDCA (ursodeoxycholic acid) related substances such as CA (cholic acid), DCA(deoxycholic acid), CDCA (chenodeoxycholic acid) and LCA (lithocholic acid) in raw material and pharmaceutical formulation.Methods: The method was validated for specificity, linearity, accuracy, precision, robustness. A triple quadrupole mass detector wasemployed, equipped with an ESI (electrospray ionization) source operated in the negative ion mode. The chromatographic systemconsisted of a Symmetry C18 column (150 mm × 4.6 mm, id; particle size 5 µm) and methanol-acetonitrile-ammonium acetate (pH 7.6;10 mM) (40:40:20, v/v/v) as the mobile phase. The chromatographic conditions were 25 uL injection volume, flow rate of 0.4 mL/minand column temperature set at 35 °C. Key findings: The method requires a minimum sample amount and presents very low LOD(limits of detection) for CA (0.29 ng/mL), DCA (0.59 ng/mL), CDCA (0.13 ng/mL) and LCA (0.44 ng/mL) in comparison to LCmethods coupled to different detectors like UV (ultraviolet), fluorescence and refractive index. Conclusions: The developed andvalidated LC-MS/MS method for the determination of UDCA and related substances in raw material and in a suspension wasadvantageous since it required a minimum sample amount. In turn, it could be used as a stability indicating method.